Exploring impulse work and active analysis in practice. Issue 1 (2nd January 2019) - Beddie, Melanie
ABSTRACT: Reading Sharon Carnicke's research about Active Analysis (2010, 2016) led me to make connections between this technique and my own directing and teaching practice. Bella Merlin too records a process she encountered in Russia which emerges from the work of Maria Knebel (Merlin 2001). This description also resonated with me strongly in my use of Impulse Work, a term that Melbourne theatre practitioners commonly use to denote a particular type of physical and spatial improvisation. It was from this context that I approached the workshop offered by Sharon Carnicke at The S Word: A Practical Acting Laboratory in April 2018. I was interested to discover in what ways the approach taken by Maria Knebel and taught by Carnicke connected to my own experiences of incorporating Impulse Work into my work on the floor with actors and with students. The investigation of the growth and adaption of forms of Impulse Work, allows a pattern of comparable approaches across a range of directors and teachers, both locally and globally, to emerge. This article suggests the diverse sources for the technique which have been synthesized by Melbourne practitioners over the last four decades. My research into the lineages of Impulse Work and my involvement in the workshop with Carnicke leads me to suggest that this technique shares key principles with Active Analysis and offers an excellent training and preparation for the application of Active Analysis in the rehearsal room.